(untitled) (Bangladesh Agronomy Journal, 2018)
A field experiment was conducted in Sher-e-Bangla Agricultural University research field of Bangladesh during December 2012 to May 2013. This experiment was tested for two planting method consisting CM planting method (P1) and System of Rice Intensification (SRI) planting method (P2) against five rice (Oryza sativa) varieties named BR 16 (V1), BRRI dhan29 (V2), BRRI dhan50 (V3), BRRI hybrid dhan2 (V4) and Heera 4 (V5). The experiment was laid out in split-plot design with three replications. All yield parameters showed the highest for SRI with higher effective tillers hill-1 (41.13), longer panicle (28.15 cm), higher total grains panicle-1 (216.89), number of filled grains panicle-1 (166.82) as a result 10.17and 12.5% higher grain yield and straw yield, respectively were observed in SRI than the conventional method. Bangladesh Agron. J. 2017, 20(2): 75-80